Difficult biliary cannulation in ERCP procedures with or without trainee involvement: a comparative study - Wang, Xu; Luo, Hui; Tao, Qin; Ren, Gui; Wang, Xiangping; Liang, Shuhui; Zhang, Linhui; Chen, Long; Shi, Xin; Guo, Xuegang; Pan, Yanglin (Endoscopy, 2021)
Background The 5–5–1 criteria (> 5 minutes – 5 cannulation attempts – 1 unintended pancreas duct cannulation) were proposed by the European Society of Gastrointestinal Endoscopy to define difficult biliary cannulation. However, the criteria may be inappropriate for trainee-involved procedures. We developed criteria for difficult cannulation in trainee-involved procedures.Methods Patients undergoing biliary cannulation with or without trainee involvement were eligible. Procedures that might be too easy (e. g. fistula) or too difficult (e. g. altered anatomy) were excluded. The primary outcome was difficult cannulation, defined as cannulation time, attempts, or inadvertent pancreatic duct (PD) cannulation exceeding the 75 % percentile of each variable. Propensity score matching (PSM) analysis was used.Results After PSM, there were 1596 patients in each group. Trainee-involved procedures had longer median (interquartile range [IQR]) cannulation time (7.5 [2.2–15.3] vs. 2.0 [0.6–5.2] minutes), and more attempts (5 [2–10] vs. 2 [1–4]) and inadvertent PD cannulation (0 [0–2] vs. 0 [0–1]) vs. procedures without trainee involvement (all P < 0.001). The 15–10–2 criteria for difficult cannulation were proposed for trainee-involved cannulation and the 5–5-1 criteria were nearly confirmed for cannulation without trainee involvement. The proportions of difficult cannulation using these respective criteria were 35.5 % (95 % confidence interval [CI] 33.2 %–37.9 %) and 31.8 % (95 %CI 29.5 %–34.2 %), respectively (odds ratio 1.18 [95 %CI 1.02–1.37]). Incidences of post-ERCP pancreatitis following difficult cannulation were comparable (7.8 % [95 %CI 5.7 %–10.3 %] vs. 9.8 % [95 %CI 7.4 %–12.8 %], respectively).Conclusion By using the 75 % percentiles as cutoffs, the proposed 15–10–2 criteria for difficult cannulation could be appropriate in trainee-involved procedures.